Synthesis and Characterization of Benzoic Acid 2-Salicylidene Complexes with Selected Metal Ions (Journal of the College of Basic Education, 2022)
Salicylaldehyde was reacting with 2-amino benzoic acid to produce the Schiff base ligand benzoic acid 2-salicylidene (L). The prepared ligand was identified by Microelemental Analysis, FT.IR and UV-Vis spectroscopic techniques. A new complexes of Co(II),Ni(II),Cu(II) and Zn(II) with Schiff base was prepared in aqueous ethanol with a (1:1) M:L. The prepared complexes were characterized using flame atomic absorption, (C.H.N) Analysis, FT.IR and UV-Vis spectroscopic methods as well as magnetic susceptibility and conductivity measurements. Biological activity of the ligand and complexes against three selected types of bacteria were also examined. Some of the complexes exhibit good bacterial activities. From the obtained data the tetrahedral structure was suggested for all prepared complexes.